Risk Analysis of Occupational Safety and Health (OSH) in the Brick Molding Process in Tungkaran Village Based on the Guidelines of OSH Risk Management for Small and Medium Enterprises in ASEAN Member States - Restiana Kartika Mantasti Hapsari; Ihya Hazairin Noor; Assyifa Aulia Rahmini; Fitrie Masykuri; Hartati, Hartati; Nella Yaliza; Yuan Pariasi (Jurnal EduHealth, 2025)
The implementation of Occupational Safety and Health (OSH) is crucial in the manufacturing industry, including the brick molding process, given the high potential for hazards that can disrupt operations and workers' well-being. Although previous research has analyzed hazards in similar industries, there has been no comprehensive study applying the HIRARC method to all stages of the brick molding process in Tungkaran Village, Martapura. This study aims to identify, assess, and control OSH risks based on the OSH Risk Management guidelines for ASEAN SMEs. A qualitative descriptive approach was used, with data collected through direct observation and structured interviews with 5 respondents. The HIRARC analysis identified 40 potential hazards. A total of 10% were categorized as high risk, 82.5% as moderate, and 7.5% as low. The highest risks were found in the raw material measuring, mixing, transportation, and brick arrangement stages. Other significant hazards include dust exposure, non-ergonomic work postures, and an untidy work environment. The brick molding process has a significant level of OSH risk. Comprehensive control through the use of PPE.